DELAY DIFFERENTIAL OPERATORS AND SOME SOLVABLE MODELS IN LIFE SCIENCES - (:unkn) unknown (ANKARA UNIV, FAC SCI, 2017)
Using the methods of the spectral theory of differential operators in Hilbert spaces L-2-solvability of some models arising in mathematical biology are investigated. Particularly, concrete solvable models are given.
Keywords: Hilbert space and direct sum of Hilbert spaces; differential; bounded and boundedly solvable operators; Hutchinson; Houseflies; Drug-free and medical models; 1ST-ORDER